Corporate Governance and Financial Performance of Banks: Evidence from Nigeria - Ogege S.; Boloupremo T. (Hyperion Economic Journal, 2014)
Banks are the backbones of any economy therefore it is of immense importance for economies to possess a healthy and buoyant banking system with effective corporate governance practices. In Nigeria, the Central Bank replaced the past governance codes with the CBN code (2012). Therefore this study examines corporate governance and financial performance in Nigerian banks, using this new code. The main issues in this study are: what is the relationship between board size and financial performance of banks in Nigeria? What is the effect of the proportion of non- executive directors on the financial performance of banks in Nigeria? To what extent is the corporate governance disclosure of banks in Nigeria in compliance to CBN governance code (2012)? Does a relationship actually exist between banks that disclose on corporate governance and their financial performance in Nigeria? These questions were answered by examining the yearly published reports of the listed banks in Nigeria. In examining whether or not there is a relationship between corporate governance and the financial performance of the banks, this research employed the regression analysis method to determine the relationship. However, the variables that was employed for corporate governance are: board size, board composition (the ratio of non-executive directors to total directors), and corporate governance disclosure index. Variables used in this study for examining the financial performance of these banks were the financial accountant measure for performance. These measures are return on equity (ROE) and return on asset (ROA). In examining the level of compliance of the banks in this study to the CBN (2012) governance code, the research employed the content analysis method. Employing the content analysis, a disclosure index was formed and the annual report for each bank was examined using the CBN code of corporate governance (2012) as a guide. The results of the study showed that a positive relationship exists between the corporate governance variables and the performance variables.